Smart Education Training Implementasi Positive Discipline Bagi Tenaga Pendidik dalam Membangun Karakter Siswa - Leonardo Snanfi , Ferinandus; Qomarrullah, Rif'iy; Sokoy, Fredrik; Wulandari S., Lestari (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the main challenges faced by prospective educators is the limited understanding and application of Positive Discipline in the educational process, which hampers optimal character development in students. This community service program aims to enhance the capacity of Primary School Teacher Education (PGSD) students at Universitas Terbuka (UT) Jayapura through Smart Education training on the implementation of Positive Discipline as a strategy to build students’ integrity, responsibility, and independence. The activity was conducted using a participatory approach through workshops, interactive discussions, and case study simulations. The results showed an 85% increase in participants’ understanding of Positive Discipline concepts, as well as improved skills in applying such approaches in educational settings. Post-training evaluations also revealed positive changes in participants’ thinking patterns regarding educational communication and the importance of early character education. This program contributes significantly to preparing future teachers who are oriented toward character development and a more humanistic school culture.